2020
DOI: 10.1039/d0dt01851a
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+ luminescence of Gd(Zn,Mg)B5O10 pentaborate under high pressure

Abstract: Results of X-ray diffraction studies of Gd(Mg0.95 x,ZnxMn 0.05)B5O10 down-converting phosphor as a function of Mg-Zn composition are presented. Lattice parameters and unit cell volumes of GdMg0.95-xZnxMn0.05B5O10 pentaborates are examined....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The blue shift of observed broad-band PL also provides a strong support for its assignment to the Mn 3+ dopant as a d 4 system. Indeed, should this luminescence be associated with 4 T 1 → 6 A 1 transitions of Mn 2+ , a red PL shift should have been seen, in accordance with Tanabe–Sugano diagrams for d 5 systems as well as several experimental results, as for example, shown in refs and .…”
Section: Resultssupporting
confidence: 87%
“…The blue shift of observed broad-band PL also provides a strong support for its assignment to the Mn 3+ dopant as a d 4 system. Indeed, should this luminescence be associated with 4 T 1 → 6 A 1 transitions of Mn 2+ , a red PL shift should have been seen, in accordance with Tanabe–Sugano diagrams for d 5 systems as well as several experimental results, as for example, shown in refs and .…”
Section: Resultssupporting
confidence: 87%
“…The pressure coefficient of PL energy is equal to around −74 cm –1 /GPa. Similar behavior was also observed in the Mn 2+ -doped pentaborate sample under high pressure . As well, due to the increase in pressure, the position of the low-temperature phonon line is slightly red-shifted, from its initial position of 709 to 714 nm.…”
Section: Resultssupporting
confidence: 81%
“…Amorphization of the nanocrystallites is reversible, although only partially since after decompression, the sample does not return to the initial crystallographic orthorhombic structure. Previously, it was observed that for Mn 2+ dopant, having the same d 5 electronic structure as Fe 3+ , in several materials (jervisite NaScSi 2 O 6 , 42 pentaborate GdZnB 5 O 10 , 41 and Tb 3 Al 5 O 12 garnet 48 ), pressure application lead to the luminescence quenching, which was associated with pressureinduced crossing between the luminescent 4 T 1g emitting level with the nonluminescent, strongly coupled to the lattice 2 T 2g level. Pressure-induced decrease in the decay time of Mn 2+ in ZnS was also observed in ZnS.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The energy levels of Mn 2+ ions can be represented by the Tanabe–Sugano diagram. 40,41 The positions of the energy levels are determined by the Racah parameters B and C and the crystal field splitting degree ( D q ), 18,34 which can be specifically calculated from the energy levels of the excitation spectra in Fig. S6† and the following equations: 40 6A 1 ( 6 S) → 4 E( 4 D) = 17 B + 5 C 6A 1 ( 6 S) → 4 A 1 , 4 E( 4 G) = 10 B + 5 C 6A 1 ( 6 S) → 4 T 2 ( 4 G) = −10 D q + 18 B + 6 C − (38 B 2 /10 D q )…”
Section: Resultsmentioning
confidence: 99%
“…17 By introducing the above ions, researchers have designed a variety of new types of optical pressure sensing phosphors, such as BaLi 2 Al 2 Si 2 N 6 :Eu 2+ , Gd(Zn,Mg)B 5 O 10 :Mn 2+ , Y 6 Ba 4 (SiO 4 ) 6 F 2 :Ce 3+ and Ca 2 Gd 8 Si 6 O 26 :Ce 3+ . 8,[18][19][20] These optical pressure sensing phosphors, although have high sensi-tivities, are very prone to errors when calibrating pressure through movement in the central peak position alone. Thus, designing high-sensitivity, multi-mode optical pressure sensing phosphors still involves challenges.…”
Section: Introductionmentioning
confidence: 99%